2016
DOI: 10.3390/ijgi5020015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Land Use/Land Cover Changes and Urban Sprawl in Al-Khobar, Saudi Arabia: An Analysis of Multi-Temporal Remote Sensing Data

Abstract: Abstract:While several studies examined land use and land cover changes in the central and western parts of Saudi Arabia, this study is the first to use remote sensing data to examine the decadal land cover changes in Saudi Arabia's eastern coastal city of Al-Khobar between 1990 and 2013. Specifically, it utilized ISODATA classification method to classify Landsat TM, ETM+, and OLI data collected (2013) indicates a high rate of urban sprawl and the city dispersing near the outskirts and towards the neighboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 60 publications
3
72
0
Order By: Relevance
“…Therefore, the cities with higher increasing rates of SUHII should pay more attention to protect the terrestrial ecosystems. In this study, the continuous and rapid urbanization of the 10 cities was similar with other cities according to previous studies [56][57][58][59]. Future studies will focus on UEs on environment at regional or global scales.…”
Section: The Relationships Between Suhii and ∆Evimentioning
confidence: 51%
“…Therefore, the cities with higher increasing rates of SUHII should pay more attention to protect the terrestrial ecosystems. In this study, the continuous and rapid urbanization of the 10 cities was similar with other cities according to previous studies [56][57][58][59]. Future studies will focus on UEs on environment at regional or global scales.…”
Section: The Relationships Between Suhii and ∆Evimentioning
confidence: 51%
“…Although the causes of these changes were not assessed in this work, recent studies on LULCC [12,25,26] that include the evaluation of NPAs [27,28] and their surrounding areas [31] have shown that deforestation due to overexploitation, uncontrolled logging, agricultural activities, consumer demand, fires, pests, and urban growth, as well as natural phenomena arising from climate change, are some of the main factors that influence the loss of vegetation in Mexico [2]. In other areas, the increase in land cover changes has been caused by the rapid population growth, the multiplication of human settlements, and regional economic development [8- 10,64]. Likewise, the highest percentages of change and transition occurred between 1973, 1986 and 2000, coincide with a period of high deforestation in Mexico [34,40], as proposed in one of the hypotheses raised in this work.…”
Section: Land Use-cover Changes Within the Natural Protected Area Altmentioning
confidence: 99%
“…Rapid urbanization and urban sprawl have a significant impact on conditions of urban land use changes due to the increasing demands for the construction of new residential, commercial, utility, and transport infrastructures [3,4]. Urbanization is a process related to population increase in urban regions that is associated with settlement increases and automatically reduces vegetation areas due to limited land [5].…”
Section: Introductionmentioning
confidence: 99%